Balancing Acts: Jordan’s Remarkable Stability Amidst Regional Conflict and Humanitarian Response - Gabbay, Shaul M. (Advances in Social Sciences Research Journal, 2023)
This paper examines the Hashemite Kingdom of Jordan’s nuanced balancing act in maintaining stability amidst regional conflict and an unprecedented refugee crisis. It explores Jordan’s multifaceted approach, which encompasses astute governance, economic innovation, social cohesion, and humanitarian outreach in the face of challenges posed by the Syrian crisis and the resultant demographic shifts. Through a comprehensive analysis of policy responses, economic strategies, and social integration efforts, the paper underscores Jordan’s resilience and strategic diplomacy. It further discusses how Jordan’s leadership under King Abdullah II has steered the nation towards a sustainable future, while navigating complex regional dynamics and upholding its humanitarian commitments.